Ca2+, Astrocyte Activation and Calcineurin/NFAT Signaling in Age-Related Neurodegenerative Diseases - Sompol, Pradoldej; Norris, Christopher M. (Frontiers in Aging Neuroscience, 2018)
Mounting evidence supports a fundamental role for Ca2+ dysregulation in astrocyte activation. Though the activated astrocyte phenotype is complex, cell-type targeting approaches have revealed a number of detrimental roles of activated astrocytes involving neuroinflammation, release of synaptotoxic factors, and loss of glutamate regulation. Work from our lab and others has suggested that the Ca2+/calmodulin dependent protein phosphatase, calcineurin, provides a critical link between Ca2+ dysregulation and the activated astrocyte phenotype. A proteolyzed, hyperactivated form of CN appears at high levels in activated astrocytes in both human tissue and rodent tissue around regions of amyloid and vascular pathology. Similar upregulation of the calcineurin-dependent transcription factor NFAT4 also appears in activated astrocytes in mouse models of Alzheimer’s disease and traumatic brain injury. Major consequences of hyperactivated calcineurin/NFAT4 signaling in astrocytes are neuroinflammation, synapse dysfunction, and glutamate dysregulation/excitotoxicity, which will be covered in this review.